Acute gangrenous colitis: a surgical dilemma - Kulkarni, Apoorva (International Surgery Journal, 2023)
Acute gangrenous colitis is a rare entity in children. Amoebic colitis and ischemic colitis are two common causes in children. We present the case of a 7-year-old boy who developed gangrene of caecum and ascending colon and underwent exploratory laparotomy and re-exploration and stomas had to be done. The cause of gangrene remained undiagnosed.